HBV immune tolerance of HBs-transgenic mice observed through parabiosis with WT mice - Zhang, Wendi; Sun, Haoyu; Sun, Rui; Lian, Zhexiong; Wei, Haiming; Tian, Zhigang; Chen, Yongyan (Frontiers in Immunology, 2022)
It was extensively recognized that central tolerance to HBV exists in HBs-transgenic (Tg) mice, however, the immune response to HBV vaccine may be inspired in adult HBs-Tg mice after boosting with potent adjuvants, leaving a mystery to explore its immune tolerance. Here, WT-HBs-Tg parabiotic mice model was generated by conjoining WT (donor) and HBs-Tg (host) mouse via parabiotic surgery, in order to see how immunocompetent WT mice naturally respond to HBV, and how tolerant HBs-Tg mice influence the anti-HBV immunity from WT mice. It was found that WT CD8+ T cells markedly accumulated into the liver of HBs-Tg parabionts, and importantly, almost all HBsAg-specific CD8+ T cells derived from WT but not HBs-Tg mice, making a clear separation of a normal immune response from WT donor and a tolerant response by recipient host. Further, in the absence of host but not donor spleen, HBsAg-specific CD8+ T cells disappeared, indicating that host spleen was the indispensable site for donor HBsAg-specific CD8+ T cell priming though its mechanisms need further study. We found that donor CD4+ T helper cells were necessary for donor HBsAg-specific CD8+ T cell response by CD4-deficiency in WT or in HBs-Tg mice, indicating that an immune response was elicited between CD4+ T helper cells and CD8+ cytotoxic T cells of donor in the host but not donor spleen. It was noted that compared to donor CD4+ T cells, host CD4+ T cells were characterized with more tolerant features by harboring more CD25+Foxp3+ Tregs with higher expression of PD-1 and TIGIT in the spleen of HBs-Tg parabionts, which exhibited suppressive function on CD8+ T cells directly. Moreover, the Th1/Treg ratio was enhanced after parabiosis, suggesting that donor T helper cells may overcome the negative regulation of host Tregs in host spleen. In conclusion, both incompetent anti-HBV CD8+ T cells and insufficient help from CD4+ T cells are the major mechanisms underlying immune tolerance in HBs-Tg mice which helps explain HBV persistence.